Ox-LDL Aggravates the Oxidative Stress and Inflammatory Responses of THP-1 Macrophages by Reducing the Inhibition Effect of miR-491-5p on MMP-9 - Liao, Yiling; Zhu, Enzheng; Zhou, Wanxing (Frontiers in Cardiovascular Medicine, 2021)
Background: Oxidized low-density lipoprotein (ox-LDL) can induce oxidative stress and inflammatory responses in macrophages to facilitate the genesis and development of atherosclerosis. However, the intermediate links remain unclear. MiR-491-5P can inhibit matrix metalloproteinase 9 (MMP-9); however, it remains unclear whether ox-LDL enhances MMP-9 expression and aggravates the oxidative stress and inflammatory responses under the mediating effect of miR-491-5P. Method: THP-1 macrophages were divided into 10 groups: blank (control), model (ox-LDL), miR-491-5P high-expression (miR-491-5P mimic), miR-491-5P control (mimic-NC), MMP-9 high-expression (MMP-9-plasmid), MMP-9 control (plasmid-NC), miR-491-5P+plasmid-NC, miR-491-5P+ MMP-9-plasmid, MMP-9 gene silencing (MMP-9-siRNA), and gene silencing control (siRNA-NC). The cells were transfected for 48 h and then treated with 50 µg/mL of ox-LDL for 24 h. MMP-9 mRNA and miR-491-5P expression levels in the cells were detected using reverse transcription-quantitative polymerase chain reaction, and the MMP-9 levels were detected with western blotting. The levels of oxidative stress factors (malondialdehyde [MDA]), reactive oxygen species (ROS), and antioxidant factors (superoxide dismutase [SOD]), and the expression levels of inflammatory factors (tumor necrosis factor [TNF-α] and interleukin-1β and -6 [IL-1β and IL-6]) in the supernatant were detected with enzyme-linked immunosorbent assay. Results: MDA, ROS, TNF-α, IL-1β, IL-6, and MMP-9 levels were increased, SOD activity was reduced, and miR-491-5P expression was downregulated in the ox-LDL group compared to the control group. In the miR-491-5P mimic group, the MDA, ROS, TNF-α, IL-1β, IL-6, MMP-9 mRNA and protein levels were downregulated, and SOD activity was enhanced compared to the ox-LDL group. MMP-9-plasmid elevated the MDA, ROS, TNF-α, IL-1β, IL-6, MMP-9 mRNA and protein levels, and downregulated SOD activity and miR-491-5P expression. Following transfection with MMP-9-siRNA, the MMP-9-plasmid outcomes were nullified, and the resulting trends were similar to the miR-491-5p simulation group. Oxidative stress and inflammatory responses were higher in the miR-491-5P mimic+MMP-9-plasmid co-transfection group than in the miR-491-5P mimic group. Conclusion: Ox-LDL aggravates the oxidative stress and inflammatory responses of THP-1 macrophages by reducing the inhibition effect of miR-491-5p on MMP-9.